Phenylhydrazine‐induced anaemia reduces subcutaneous white and brown adipose tissues in hypothalamic obese rats. Issue 6 (6th May 2022) - de Souza, Domwesley Wendreo; Ceglarek, Vanessa Marieli; Siqueira, Bruna Schumaker; Volinski, Caroline Zanella; Nenevê, Juliane Zanon; Arruda, João Paulo de Amorin; Vettorazzi, Jean Franciesco; Grassiolli, Sabrina
Abstract : New Findings: What is the central question of this study? Can an anaemic state modify adiposity and metabolic parameters in hypothalamic obese rats? What is the main finding and its importance? Hypothalamic obese rats do not display iron deficiency. However, the pharmacological induction of anaemia in hypothalamic obese rats resulted in reduced adiposity, characterized by a decrease in subcutaneous white and brown adipose tissue depots. These findings suggest that iron imbalance in obesity may elevate lipolysis. Abstract: Iron imbalance is frequent in obesity. Herein, we evaluated the impact of anaemia induced by phenylhydrazine on adiposity and metabolic state of hypothalamic obese rats. Hypothalamic obesity was induced by high doses of monosodium glutamate (MSG; 4 g/kg) administered to neonatal male rats ( n  = 20). Controls (CTL; non‐obese rats) received equimolar saline ( n  = 20). Rats were weaned at 21 days of life. At 70 days, half of the rats received three intraperitoneal doses of phenylhydrazine (PHZ; 40 mg/kg/dose) or saline solution. Body weight and food intake were followed for 4 weeks after PHZ administration. At 92 days, rats were killed and blood was collected for microcapillary haematocrit (Hct) analysis and plasma quantification of glucose, triglycerides, total cholesterol and iron levels. The liver, the spleen, and the white (WAT) and brown (BAT) adipose tissues were excised, weighed and used for histology. MSG‐treated rats developed obesity, hypertriglyceridaemia and insulin resistance, compared to CTL rats, without changes in iron levels and Hct. PHZ administration reduced plasma iron levels and promoted similar tissue injuries in the spleen and liver from MSG and CTL rats. However, in MSG‐treated rats, PHZ decreased fasting glucose levels and Hct, as well as diminishing the subcutaneous WAT and BAT mass. Although MSG‐obesity does not affect plasma iron levels and Hct by itself, PHZ‐induced anaemia associated with obesity induces a marked drop in subcutaneous WAT and BAT mass, suggesting that iron imbalance may lead to increased lipolytic responses in obese rats, compared to lean rats.